Pengaruh Konseling Behavioristik Terhadap Sikap Keuletan pada Siswa Kelas VIII SMP Negeri 3 Batukliang Utara - Gunawan, I Made; Endriani, Ani; Malina, Ria (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2019)
This study aimed to study the effect of Behavioristic Counseling on students’ tenacity attitudes of class VIII at SMPN 3 Batukliang Utara. This research used the experimental method. Samples of the study were 6 students who had a low tenacity attitude. Data collection technique used was questionnaire, observation, interview, and documentation. The data analysis technique used the t-test formula. The results of the study showed that the value of t count was 2.890 and the value of t table was 2.015 at the level of significance 5% with N = 5, in which the value of t count was greater than the value of the t table (2.890> 2.015). So, it can be concluded that there is an effect of Behavioristic Counseling on students’ tenacity attitudes of class VIII at SMPN 3 Batukliang Utara